Covid-19 and diet: an evaluation of information available on internet in Italy - Ambra, Roberto; Canali, Raffaella; Pastore, Gianni; Natella, Fausta (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: During Coronavirus disease 2019 (Covid-19) Italy experienced deep lockdown with closure of almost all activities, with the exception for food shops and few others. During this quarantine, alteration of dietary habits occurred, due to the changes in food availability and mandatory meal house-consumption. The change in dietary habits could somehow be directed by freely accessible information available on internet.  Thus, s we evaluated the type and the scientific quality of the information provided to the Italian population by the most visible web sites found on google, relating diet in Covid-19 time.Methods: we systematically perform a reliability and content analysis of Italian language websites using google as search engine and a combinations of diet/nutrition/Covid-19 as search termsResults: 88 webpages were included in the study, the great part representing newspaper webpages. Institutional webpages, despite having high scientific quality, did not have high visibility. Generally, all the other webpages reported information of medium-quality scientific level.Conclusion: finding appropriate solutions to redirect the population’s attention to more reliable and accessible information is mandatory.